Electrical studies for trades - Herman, Stephen L. (Thomson / Delmar Learning, 2006)
Electrical Studies for Trades is ideal for current and future service technicians in fields such as air conditioning and refrigeration, construction, and facilities management who require practical knowledge of electricity. This book begins with an overview of basic electricity concepts rather than introducing complex mathematical calculations. From this starting point, readers proceed directly to "must-know" information, including how to determine wire sizes and make a variety of common switch connections. Different types of electrical power panels are also examined in detail. Discussion of general wiring practices and circuit protectors, as well as an introduction to transformers and three-phase and single-phase motors, rounds out the comprehensive coverage.